The Influence of Implementing Continuing Professional Development (CPD) on Knowledge and Skills in Providing Nursing Care - Nurlely Triwahyuni; Agusta Dian E; Nurwijayanti Nurwijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: In Indonesia, the number of Patient Safety Incidents (PSIs) reached 7,465 cases in 2019, comprising 171 deaths, 80 severe injuries, 372 moderate injuries, 1,183 minor injuries, and 5,659 cases with no injuries. Objective: This study aims to determine the effect of Continuing Professional Development (CPD) on improving nurses' knowledge and skills in providing quality nursing care at RSUD Aji Muhammad Parikesit. Methods: This research employed a quasi-experimental, two-group pre-test-post-test control group design. A proportional probability sampling technique was used, with 102 respondents divided into two groups: 51 in the intervention group and 51 in the control group at RSUD Aji Muhammad Parikesit. Data were analyzed using the Paired T-Test with a significance level of p-value ≤ 0.05 at a 95% confidence level. Results: The analysis of nurses' knowledge using the Paired T-Test showed a p-value of 0.000 < α = 0.05 in the intervention group, while the control group had a p-value of 0.307 > α = 0.05. For nurses' skills, the intervention group had a p-value of 0.000 < α = 0.05, while the control group showed a p-value of 0.083 > α = 0.05. Conclusion: CPD plays a crucial role in the professional development of nurses and can serve as a strategy to improve the quality of healthcare services in hospitals. Future studies are recommended to control for confounding variables to achieve more accurate results and to extend the duration and coverage of CPD to sustain its long-term impact.